Effect of Doping Metals on the Structure of PEO Coatings on Titanium. (19th June 2018) - Sakhnenko, Nykolay D.; Ved', Maryna V.; Karakurkchi, Ann V.
Abstract : The structure and properties of the oxide films formed on titanium alloys by means of plasma-electrolytic oxidizing in alkali electrolytes based on pyrophosphates, borates, or acetates of alkali metals with the addition of dopants' oxides or oxoanions of varying composition have been studied. Anodic polarization in the spark discharge (microarc) mode at application of interelectrode potential 90 to 160 V has been used to obtain mixed-oxide systems TiO x ·WO y, TiO x ·MoO y, TiO x ·ZrO2, and TiO x ·V2 O5 . The possibility to obtain the oxide layers containing the alloying elements by the modification of the composition of electrolytes has been stated. The chemical and phase composition as well as the topography, the microstructure, and the grain size of the formed layers depend on the applied current, interelectrode voltage, and the layer chemical composition. The effect of formed films composition on the resistance of titanium to corrosion has been discussed. Catalytic activity of mixed-oxide systems was determined in the model reaction of methyl orange dye MO photodestruction.